Reversibly compressible and freestanding monolithic carbon spherogels. (November 2019) - Salihovic, Miralem; Zickler, Gregor A.; Fritz-Popovski, Gerhard; Ulbricht, Maike; Paris, Oskar; Hüsing, Nicola; Presser, Volker; Elsaesser, Michael S.
Abstract: We present a versatile strategy to tailor the nanostructure of monolithic carbon aerogels. By use of an aqueous colloidal solution of polystyrene in the sol-gel processing of resorcinol-formaldehyde gels, we can prepare, after supercritical drying and successive carbonization, freestanding monolithic carbon aerogels, solely composed of interconnected and uniformly sized hollow spheres, which we name carbon spherogels. Each sphere is enclosed by a microporous carbon wall whose thickness can be adjusted by the polystyrene concentration, which affects the pore texture as well as the mechanical properties of the aerogel monolith. In this study, we used monodisperse polystyrene spheres of approximately 250 nm diameter, which result in an inner diameter of the final hollow carbon spheres of approximately 200 ± 5 nm due to shrinkage during the carbonization process. The excellent homogeneity of the samples, as well as uniform sphere geometries, are confirmed by small- and angle X-ray scattering. The presence of macropores between the hollow spheres creates a monolithic network with the benefit of being reversibly compressible up to 10% linear strain without destruction. Electrochemical tests demonstrate the applicability of ground and CO2 activated carbon spherogels as electrode materials. Graphical abstract: Image 1